Developmental psychology : how nature and nurture interact - Richardson, Keith, 1943- (L. Erlbaum, 2000)
The developmental psychology text covers such topics as Darwinian dichotomies and their dissolution, dynamic systems theories, the creation and origins of knowledge, and coupled primal and plastic interactions in humans.